2021 global burden of disease study: a comprehensive analysis of glaucoma in the middle-aged and older adult population at global, regional, and national levels - Li, Xiang; Huang, Guo-xin; Li, Ran; Zhang, Zhi-Jie; Zhang, Si-Qi; Zhu, Lei; Tang, Jia-feng; Wang, Jia-qi; Wang, Xiong (Frontiers in Public Health, 2025)
BackgroundGlaucoma is a leading cause of irreversible blindness globally, with a particularly significant impact on middle-aged and older adults (aged 45 years and above), substantially affecting their quality of life and imposing considerable socio-economic burdens. Comprehensive assessments of the burden of glaucoma in this age group at global, regional, and national levels are crucial for shaping health policies and optimizing resource allocation.MethodsData on the burden of glaucoma among individuals aged 45 years and above were obtained from the 2021 Global Burden of Disease (GBD) study. The Average Annual Percent Change (AAPC) was used to evaluate trends in glaucoma burden from 1990 to 2021 among this population. The Slope Index of Inequality (SII) and the Concentration Index (CI) were employed to analyze both absolute and relative health inequalities in the burden of glaucoma. An Age–Period–Cohort model focusing on the 45+ age group was fitted using the NORDPRED package to predict the future burden of glaucoma. Additionally, frontier analysis was conducted to assess the relationship between the burden of glaucoma and socio-demographic development in the older adult population, using non-parametric Data Envelopment Analysis (DEA) to define a boundary based on the level of development for the minimal achievable burden.ResultsIn 2021, there were 5.34 million cases of glaucoma among the global population aged 45 years and above (95% UI: 4.22–6.45 million), with an age-standardized prevalence rate (ASPR) of 889.3 per 100,000 population (95% UI: 700.2–1078.5). The AAPC for glaucoma in this age group from 1990 to 2021 was −0.82 (95% CI: −0.85 to −0.8), indicating a downward trend in both ASPR and age-standardized DALY rate (ASDR) globally among middle-aged and older adults. At the regional level, areas with lower Socio-Demographic Index (SDI) exhibited higher ASPRs, whereas high SDI regions recorded lower rates. Nationally, countries such as Niger and Nigeria demonstrated the highest age-standardized rates within this demographic. Health inequality analyses revealed that countries with lower SDI bear a disproportionately higher burden of glaucoma among middle-aged and older adults. Predictions indicate that although the number of global cases in this age group may rise, the overall burden of glaucoma is expected to gradually decline.ConclusionAs one of the leading causes of blindness among middle-aged and older adults worldwide, glaucoma remains a significant public health concern. Although the absolute number of cases in individuals aged 45 years and above continues to rise due to population growth and aging, both the ASPR and ASDR have shown declining trends. This decline reflects meaningful progress in the prevention, diagnosis, and management of the disease. To address the ongoing increase in case numbers, targeted policy interventions are needed to ensure effective prevention and management strategies, contributing to the achievement of global sustainable development goals. Furthermore, frontier analysis identifying disparities between national development levels and the burden of glaucoma in the older adult population can aid in optimizing the allocation of global health resources.